Literature Study: The Role of Educational Psychology in Learning Science: Study Literatur : Peran Psikologi Pendidikan Dalam Pembelajaran IPA - Apriani Sijabat; Rina Devi Romauli Siahaan; Lampola Sitorus P; Sahat Renol HS (Institute of Educational, Research, and Community Service, 2023)
The purpose of this research is to understand the role of educational psychology in learning science. The method used in this research is literature review, namely by collecting information through national journals, books and other references related to the role of educational psychology in learning natural sciences. The results obtained are that educational psychology has an important role as a science that examines mental problems and one's psychological activity in relation to education. Educational Psychology as an interaction and discipline that is quite important in examining problems that interfere with or support students' souls in the science learning process, so that by understanding students' mental states, teachers can manage and try to find solutions to these problems and a teacher should have comprehensive knowledge. about educational psychology so that science learning can be carried out well